Telomerase activity associated with progression of cervical lesions in a group of Colombian patients - Andrés Felipe Castro-Duque; Nelsy Loango-Chamorro; Bayron Manuel Ruiz-Hoyos; Patricia Landázuri (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
Abstract PURPOSE To analyze the relation between the cytological findings and telomerase activity (TA). METHODS Cervical samples were evaluated and classified according to the Bethesda System. Telomerase activity was measured total product generated values (TPG) using the TRAP assay (telomeric repeat amplification protocol); data were analyzed statistically using the χ2 test, with the level of significance set at p<0.05. RESULTS The study was conducted on 102 patients. Of these, 3.9% showed normal cytological findings, 8.8% showed cervicitis; 2% showed Atypical Squamous Cells of Undetermined Significance (ASCUS); 67.6% showed Low Grade Squamous Intraepithelial Lesion (LSIL); 11.8% showed High Grade Squamous Intraepithelial Lesion (H-SIL) and 5.9% showed Squamous Carcinoma. Among telomerase-positive samples, the TPG values were cervicitis<normal<ASCUS<L-SIL<H-SIL<Carcinoma. CONCLUSION Results show increased telomerase activity with increasing severity of lesion, supporting the association between TA and type of lesion.